(untitled) (Eurasian Medical Research Periodical, 2022)
Earthworms have been used for medicinal purposes since ancient times. They have been used and most studied in Southeast Asian countries, particularly China, for 2,300 years. Chinese medicine has hundreds of recommendations for the treatment of dried, mined, or live worms. In addition, Chinese medicine has used dried earthworm powder as an ingredient in the treatment of arthrosclerosis associated with tinnitus and dizziness. These include easily digestible proteins and large amounts of unsaturated lipids, similar to the lipid content of some fish tracks. The common ingredients of earthworms can be compared to chicken eggs. Ingredients of worms are necessary for the growth of fish and the maintenance of the immune system. The purpose of this paper is to study the medicinal properties of earthworms as a treatment for human disease